2001
DOI: 10.1074/jbc.m005666200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Human β-Gal-3′-sulfotransferase That Acts on Both Type 1 and Type 2 (Galβ1–3/1–4GlcNAc-R) Oligosaccharides

Abstract: A novel sulfotransferase gene (designated GP3ST) was identified on human chromosome 2q37.3 based on its similarity to the cerebroside 3-sulfotransferase (CST) cDNA (Honke, K., Tsuda, M., Hirahara, Y., Ishii, A., Makita, A., and Wada, Y. (1997) J. Biol. Chem. 272, 4864 -4868). A full-length cDNA was obtained by reverse transcription-polymerase chain reaction and 5-and 3-rapid amplification of cDNA ends analyses of human colon mRNA. The isolated cDNA clone predicts that the protein is a type II transmembrane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 45 publications
(34 reference statements)
6
61
1
1
Order By: Relevance
“…Interestingly, Gal3ST-1 also acts on β-Gal residues in pNP-or Bn-conjugated oligosaccharides, suggesting that Gal3ST-1 essentially recognizes hydrophobic moieties including Cer, pNP, and Bn, as well as β-Gal residues. Gal3ST-2 can act on type 1, type 2, and core 1 structure, as shown by Honke et al 10) It should be noted that the enzyme can utilize not only β-Gal residues, but also Galα-O-pNP, and that LNT can be sulfated only by Gal3ST-2 (Table IV). Gal3ST-3 prefers type 2 oligosaccharides to type 1 and core 1, as shown by El-Fasakhany et al 12) Gal3ST-4 is strictly core 1-specific, as shown by us.…”
Section: Substrate Specificities Of Four Gal3stsmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, Gal3ST-1 also acts on β-Gal residues in pNP-or Bn-conjugated oligosaccharides, suggesting that Gal3ST-1 essentially recognizes hydrophobic moieties including Cer, pNP, and Bn, as well as β-Gal residues. Gal3ST-2 can act on type 1, type 2, and core 1 structure, as shown by Honke et al 10) It should be noted that the enzyme can utilize not only β-Gal residues, but also Galα-O-pNP, and that LNT can be sulfated only by Gal3ST-2 (Table IV). Gal3ST-3 prefers type 2 oligosaccharides to type 1 and core 1, as shown by El-Fasakhany et al 12) Gal3ST-4 is strictly core 1-specific, as shown by us.…”
Section: Substrate Specificities Of Four Gal3stsmentioning
confidence: 98%
“…Gal3ST transfers sulfate from PAPS to the C-3 position of Gal residues in various glycoconjugates. Four Gal3ST genes have so far been identified [9][10][11][12][13] and their genetic and biochemical characters are summarized in Table I. Honke et al 9,14) purified cerebroside 3′-sulfotransferase (Gal3ST-1) from human renal cancer cells and isolated its cDNA based on partial amino acid sequences.…”
Section: 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, some variants of ceramides are interesting too. In beta cells, ceramide is taken up and ligated with galactose by ceramide galactosyltransferase to β-galactosylceramide (GalCer) [3] and, furthermore in the Golgi apparatus, a sulphate group is linked by galactosylceramide sulfotransferase to form sulphated galactosylceramide, also called sulfatide [4]. The same process takes place in the brain and is likely to occur in the liver.…”
mentioning
confidence: 99%